Three new species of the genus Ricanula Melichar, 1898 (Hemiptera: Fulgoromorpha: Ricaniidae) from China - Ren, Lan-Lan; Stroiński, Adam; Qin, Dao-Zheng (Zootaxa, 2016)
Three new species of the genus Ricanula Melichar, 1898: R. unica sp. nov., R. fujianensis sp. nov. and R. hainanensis sp. nov. are described from south China. An identification key to Ricanula species in Chinese fauna is provided. Photographs of the adults and illustrations of genital structures of the new species are also given.